Nucleus-selective codelivery of proteins and drugs for synergistic antitumor therapy. Issue 35 (22nd August 2022) - Yang, Lan; Ma, Huijie; Lin, Shan; Zhu, Yupeng; Chen, Hui; Zhang, Ning; Feng, Xuli
Abstract : An efficient nucleus-targeted co-delivery nanoplatform with high endosomal escape ability to transport proteins and drugs into nucleus was prepared for synergistically enhanced cancer therapy. Abstract : Subcellular organelle targeted transport is of great significance for accurately delivering drugs to active sites for better pharmacological effects, but there are still a lot of challenges due to transport problems. In addition, the killing effect of one kind of drug on cells is limited. Therefore, it is necessary to develop a multifunctional nanoplatform that can co-deliver synergistic therapeutic agents. Here, we prepare a simple amphiphilic nanocarrier (LC) with rapid endosomal escape ability for nucleus-selective delivery of hydrophilic active protein deoxyribonuclease I (DNase I) and hydrophobic anticancer drug doxorubicin (DOX). LC has been applied to effectively encapsulate DNase I just by simply mixing their aqueous solutions together. In addition, DOX modified with adamantane groups via a redox-responsive linker is incorporated into the architecture of DNase I nanoformulations through host–guest interaction. This multi-component nanoplatform can quickly escape from the endolysosomes into the cytoplasm and make DNase I and DOX highly accumulate in the nucleus and consequently induce strong synergistic anticancer efficacy both in vitro and in vivo . This work illustrates a new platform for codelivery of proteins and drugs that target subcellular compartments for functions.